2016
DOI: 10.1177/1756285616670060
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropic hormone versus methylprednisolone added to interferon β in patients with multiple sclerosis experiencing breakthrough disease: a randomized, rater-blinded trial

Abstract: Background:The objective of this study was to evaluate monthly intramuscular adrenocorticotropic hormone (ACTH) gel versus intravenous methylprednisolone (IVMP) add-on therapy to interferon β for breakthrough disease in patients with relapsing forms of multiple sclerosis. Methods: This was a prospective, open-label, examiner-blinded, 15-month pilot study evaluating patients with Expanded Disability Status Scale (EDSS) score 3.0-6.5 and at least one clinical relapse or new T2 or gadolinium-enhanced lesion in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…In a small study, dexamethasone was superior to methylprednisolone and ACTH in shortening duration of relapses, but there were only 30 patients in that study [ 115 ]. More recently, a small randomized open label rater blinded study demonstrated that ACTH was more effective than intravenous methylprednisolone for relapses and had greater effects on plasma cytokines, when added to interferon beta [ 116 ]. ACTH as treatment for relapses is generally reserved for patients who are allergic to corticosteroids, develop psychosis with corticosteroid therapy or who fail to respond to treatment with corticosteroids.…”
Section: Treatment Of Human Neurologic Diseases With Melanocortinsmentioning
confidence: 99%
“…In a small study, dexamethasone was superior to methylprednisolone and ACTH in shortening duration of relapses, but there were only 30 patients in that study [ 115 ]. More recently, a small randomized open label rater blinded study demonstrated that ACTH was more effective than intravenous methylprednisolone for relapses and had greater effects on plasma cytokines, when added to interferon beta [ 116 ]. ACTH as treatment for relapses is generally reserved for patients who are allergic to corticosteroids, develop psychosis with corticosteroid therapy or who fail to respond to treatment with corticosteroids.…”
Section: Treatment Of Human Neurologic Diseases With Melanocortinsmentioning
confidence: 99%
“…1 The standard treatment is short-course, high-dose corticosteroid therapy, oral versus intravenous methylprednisolone, 2 prednisone or adrenocorticotropic hormone formulated as Acthar Gel injection. 3,4 Largely ignored historically, cognitive dysfunction was recently measured in relapsing MS patients using the Symbol Digit Modalities Test (SDMT). 5,6 In the Safety of TYSABRI Re-dosing and Treatment (STRATA), a year-long, single-arm observational safety study of natalizumab, patients were screened for progressive multifocal leukoencephalopathy (PML) at monthly infusion visits.…”
Section: Introductionmentioning
confidence: 99%
“…Several treatment options have been proposed in the literature for patients with relapses of MS 43 44. However, even if our patient did not experience further exacerbations, adrenocorticotropic hormone as a first measure and then dexamethasone and plasma exchange seem to be reliable among the most common treatments, according to published data 45–51…”
Section: Discussionmentioning
confidence: 61%